Solo Exhibition-Venice Art Biennale 2019 - Antoniou, Klitsa (My University, 2026)
Solo Exhibition-Venice Art Biennale 2019 Maleth Heaven Port: Heterotopias of Evocation Atlantropa-X Malta National Pavilion, Arsenale (With Trevor Borg and Vince Briffa) Supported by Malta Arts Council Venice, Italy